Teacher Origin and Its Influence on Thai Students’ English Proficiency and Cross-Cultural Competence - Apridayani, Aisah; Sakkanayok, Kanyanat; Sukarsih (International Journal of Multicultural Education, 2025)
This study addresses the underexplored dynamics among local Thai teachers, native English-speaking teachers (NESTs), and foreign non-native English-speaking teachers (NNESTs) in Thai English education. Conducted with 30 English majors at a southern Thai university, this phenomenological qualitative study used reflective essays and thematic analysis. Four themes emerged: Thai and NNESTs were preferred for grammar and accuracy and fostered student confidence, while NESTs were preferred for pronunciation and speaking skills. Additionally, exposure to diverse teachers enhanced cultural and communicative competence. Findings revealed the complexity of language learning experiences and unique contributions of each teacher type to student proficiency and satisfaction.